Freshwater investigations on Apid Island, Inopacan, Leyte, Philippines: results of lithotelmic investigation - Freitag, Hendrik; Zahn, Erika; Goeltenboth, Friedhelm (Annals of Tropical Research, 1999)
Preliminary investigations of some of the numerous lithotelmata found in the limestone area of Apid Island off the west coast of Leyte revealed the following facts: The majority of these lithotelmata are semi- permanent. They are partly used for human activities like washing, influencing both the pH values and the biocoenosis. pH values under undisturbed conditions range from 7 and 8. Water temperature rises and falls according to the diurnal cycle, so does the pH in those lithotelmata invested with filamentous algae of the genus Oedogonium. Neighboring lithotelmata show very different faunal composition including species usually showing long developmental cycles like dragonflies. Ostrocodes were the most abundant single species group found. The main faunal component of a phytotelmata in the form of a water-filled coconut shell were neustic collembola.